2022
DOI: 10.1002/fes3.434
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of grain yield in wheat using source–sink datasets derived from RGB and thermal infrared imaging

Abstract: Timely and efficient monitoring of crop aboveground biomass (AGB) and grain yield (GY) forecasting before harvesting are critical for improving crop yields and ensuring food security in precision agriculture. The purpose of this study is to explore the potential of fusing source–sink‐level color, texture, and temperature values extracted from RGB images and thermal images based on proximal sensing technology to improve grain yield prediction. High‐quality images of wheat from flowering to maturity under differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 133 publications
0
2
0
Order By: Relevance
“…The highest prediction result was obtained using an integrated model based on SVM, GP, LRR, and RF, with an R 2 of 0.78, which was superior to a single machine learning algorithm and independent variables without feature optimization. In terms of data-fusion yield calculation, the main approach is to use multi-sensor and multichannel data to establish a wheat-yield calculation model, and many more results have been achieved than with a single dimension, such as those of Fei et al [38], Li et al [62], Sharif et al [63], and Ma et al [64], who have studied some wheat-yield calculation models based on the fusion of multi-channel data such as RGB images, multispectral, thermal infrared images, and meteorological data. The results obtained through multiple machine learning algorithms are superior to single-channel modeling, and the calculation accuracy and robustness were more advantageous.…”
Section: Growth Environment Parametersmentioning
confidence: 99%
“…The highest prediction result was obtained using an integrated model based on SVM, GP, LRR, and RF, with an R 2 of 0.78, which was superior to a single machine learning algorithm and independent variables without feature optimization. In terms of data-fusion yield calculation, the main approach is to use multi-sensor and multichannel data to establish a wheat-yield calculation model, and many more results have been achieved than with a single dimension, such as those of Fei et al [38], Li et al [62], Sharif et al [63], and Ma et al [64], who have studied some wheat-yield calculation models based on the fusion of multi-channel data such as RGB images, multispectral, thermal infrared images, and meteorological data. The results obtained through multiple machine learning algorithms are superior to single-channel modeling, and the calculation accuracy and robustness were more advantageous.…”
Section: Growth Environment Parametersmentioning
confidence: 99%
“…For example, Wang's results show that the RF variable-screening algorithm exhibits good performance in processing wheat SPAD data [30]. The experimental results of Li et al indicated that the estimation accuracy in the wheat yield prediction model could be improved by using the LASSO variable-selection algorithm [75].…”
Section: Comparison Of Different Variable-screening Algorithmsmentioning
confidence: 99%